2018
DOI: 10.1093/jas/sky378
|View full text |Cite
|
Sign up to set email alerts
|

An acute challenge with a deoxynivalenol-contaminated diet has short- and long-term effects on performance and feeding behavior in finishing pigs1

Abstract: Mycotoxins are toxic secondary metabolites produced by various fungi and are known to contaminate animal feed ingredients especially cereals. One of the most common mycotoxins in swine diets is deoxynivalenol (DON) which is known to decrease growth performance. The objective of the present study was to evaluate the effects of single or repeated shortterm DON challenges on growth performance, and feeding behavior in finishing pigs. A total of 160 pigs were distributed to four experimental groups in two successi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 61 publications
4
24
1
Order By: Relevance
“…In this study, the DON exposure impacted the ADFI, ADG, and FCR of the pigs at 119 and 140 days of age as previously detailed by Serviento et al [27], but no impact on the performances was observed after the two-week recovery at 154 days of age. In addition, a transient impact on the microbiota composition has been observed [28].…”
Section: Discussionsupporting
confidence: 74%
“…In this study, the DON exposure impacted the ADFI, ADG, and FCR of the pigs at 119 and 140 days of age as previously detailed by Serviento et al [27], but no impact on the performances was observed after the two-week recovery at 154 days of age. In addition, a transient impact on the microbiota composition has been observed [28].…”
Section: Discussionsupporting
confidence: 74%
“…The parameters of the target CFI curve did not differ between the four treatment groups resulting in similar values for the average target DFI (Table 1). This differs from the results of Serviento et al (2018) who reported differences in the observed ADFI among the groups. Moreover, the average target DFI of the control group CC was very similar to the observed ADFI (Table 1).…”
Section: Estimation Of the Target Cumulative Feed Intakecontrasting
confidence: 99%
“…The constant reduction in DFI during feeding the DONcontaminated diet differs from the average observations of the change in DFI of Serviento et al (2018). They observed an important reduction in DFI during the first day of the challenge, and this reduction became progressively less important to surpass the DFI of the control group resulting in compensatory DFI (see Figure 4 of Serviento et al, 2018). There are two explanations for this difference.…”
Section: Characterisation Of the Feed Intake Responsementioning
confidence: 74%
See 2 more Smart Citations